Influence of Home Environment on The Academic Performance of Pupils - Olawale Abayomi Onikoyi (Indonesian Journal of Multidiciplinary Research, 2023)
The film of this study has on the influence of the home environment on the academic performance of pupils in the Isolo Local Government Area of Lagos State. The study thus examined various factors, which were likely to enhance the academic achievement of the pupils. The study then revealed that (1) parental socio-economics (2) parental level of education (3) parental motivation (4) parental income and (5) stability at home all have bearing on the academic performance of children at the primary school level. Consequently, suggestions were made for better enhancement of the academic performance of the children. However, there is no significant relationship between influences of the home environment on the academic performance of pupils in the Isolo local government area of Lagos state.